Continuous measurement of intra‐oral pH and temperature: development, validation of an appliance and a pilot study. (21st March 2015) - Choi, J. E.; Loke, C.; Waddell, J. N.; Lyons, K. M.; Kieser, J. A.; Farella, M.
Summary To describe a novel approach for continuous measurement of intra‐oral pH and temperature in individuals carrying out normal daily activities over 24 h. We designed, validated and constructed a custom‐made appliance fitted with a pH probe and a thermocouple. Six subjects wore the appliance over a 24‐h period for two non‐consecutive days, while the intra‐oral pH and temperature were measured continuously and recorded. Intra‐oral pH and temperature were very similar across different recording days, the difference being not statistically significant (P ≥ 0·14). There was a noticeable difference in the pattern of variation of pH between day and night. During the day, the mean pH was 7·3 (±0·4) and dropped markedly only after consumption of acidic food and drinks. The intra‐oral pH decreased slowly during sleep with an average pH of 6·6 (±0·4) being recorded. The difference between day and night was statistically significant (P = 0·002). The mean intra‐oral temperature was 33·9 °C (±0·9) during daytime and 35·9 °C (±0·5) during sleep (P = 0·013) with minor fluctuations occurring over 24 h. The continuous and simultaneous intra‐oral pH and temperature measurement system described in this report is reliable, easy to construct, able to measure variables over a sustained period and may serve as a future diagnostic tool in a number of applications.